2022
DOI: 10.4314/ijbcs.v16i4.24
|View full text |Cite
|
Sign up to set email alerts
|

Economic and ethnobotanical importance of the genera Albizia, Parkia and Tetrapleura(Leguminosae-Mimosoideae) in Cameroon

Abstract: People use goods and services related to Leguminosae-Mimosoideae resources to satisfy multiple needs in Cameroon. Despite some work already done, information on these goods and services remains insufficient. To date, the contribution of these plants to the needs of the population is also unknown. The objective of this study was to provide an overview of the uses of Leguminosae-Mimosoideae by rural and urban populations in Cameroon. Focus was on the genera Albizia, Parkia and Tetrapleura. Socio-economic and eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The diagnosis of the socio-economic value of spice species (I. gabonensis, R. heudelotii, T. tetraptera) in the Bertoua city and its surroundings of the East region of Cameroon showed that almost 86.2% of the actors involved in NTFP activities are women. As in the study by Tchapda et al (2022) on the Leguminosae Mimosoideae in Cameroon, the predominance of women could be explained by the fact that the surveys were carried out in markets dominated by women who are generally involved in the marketing and preparation of spices. For men, these are female activities.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The diagnosis of the socio-economic value of spice species (I. gabonensis, R. heudelotii, T. tetraptera) in the Bertoua city and its surroundings of the East region of Cameroon showed that almost 86.2% of the actors involved in NTFP activities are women. As in the study by Tchapda et al (2022) on the Leguminosae Mimosoideae in Cameroon, the predominance of women could be explained by the fact that the surveys were carried out in markets dominated by women who are generally involved in the marketing and preparation of spices. For men, these are female activities.…”
Section: Discussionmentioning
confidence: 98%
“…They are more abundant during the peak production period and the price is relatively affordable compared to the season of scarcity. In terms of marketing of T. tetraptera, only the fruits are selfconsumed and marketed by local people (Tchapda et al, 2022). Sales prices and units of measurement vary from collectors to retailers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation